Analisis Dampak Judi Online Berbasis Aktivitas Digital terhadap Kesehatan Mental dan Perilaku Sosial Generasi Muda di Indonesia - Alfani Azhard; Haris Pratama; Putri Nabawy (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
The rapid development of digital technology has significantly increased public access to online activities, including online gambling, which has emerged as a serious social problem in Indonesia. This study aims to analyze the impact of online gambling on the mental health and social behavior of young people. This research employed a descriptive method with a survey approach. Data were collected through questionnaires distributed to young respondents who had experience or exposure to online gambling activities. The findings indicate that involvement in online gambling has a significant impact on mental health disorders such as stress, anxiety, and depressive symptoms. In addition, online gambling contributes to a decline in social interaction quality, increased family conflict, social withdrawal, and reduced productivity. Behavioral changes such as impulsivity and decreased self-control were also identified among respondents. These results demonstrate that online gambling not only affects individuals psychologically but also disrupts social relationships and family harmony. Therefore, comprehensive preventive efforts are needed through digital literacy enhancement, family involvement, and psychological support services to protect young people from the negative consequences of online gambling.